Renewable energy resources in Lebanon - Houri, Ahmad (2005)
Countries of the south generally have abundant renewable and nonrenewable energy resources. Lebanon is among the few countries that are not endowed with fossil fuels in the Middle East; accordongly, it is imperative that renewable energy (RE) be looked at as aba alternative energy source. A review of the energy scene in Lebanon and available RE sources is presented. With the current status of technology and the available resources, the best renewable energy domain to focus on is the solar thermal water heating for residential houses.